2020
DOI: 10.3892/etm.2020.8995
|View full text |Cite
|
Sign up to set email alerts
|

One‑year outcomes of 27G core‑pars plana vitrectomy of idiopathic epiretinal membrane

Abstract: The present study aimed to assess the feasibility and safety of 27G core-pars plana vitrectomy (PPV) for idiopathic epiretinal membrane (IERM). A retrospective analysis was performed on 38 eyes from 38 patients with IERM with a mean age of 62.73±5.61 years. 27G core-PPV was combined with IERM and internal limiting membrane (ILM) peeling. Pre-operative and post-operative best-corrected visual acuity (BCVA) and lens density were measured. Optical coherence tomography (OCT) and OCT angiography were performed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Similar to our results, previous research reported that BCVA recovery was negatively related to the FAZ area [ 8 , 15 , 17 , 22 ] for postoperative correlation analyses. However, several studies reported controversial results that may be attributed to the varying sample sizes, instruments, and measurement depth [ 14 , 16 , 18 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, previous research reported that BCVA recovery was negatively related to the FAZ area [ 8 , 15 , 17 , 22 ] for postoperative correlation analyses. However, several studies reported controversial results that may be attributed to the varying sample sizes, instruments, and measurement depth [ 14 , 16 , 18 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The FAZ area and perimeter were significantly correlated with the baseline and postoperative BCVA. The correlation between FAZ area and baseline BCVA was also proven in previous studies ( 28 , 35 , 37 39 ) and BCVA recovery ( 28 , 37 , 40 , 41 ). Due to the differences in sample size, follow-up time, scanning depth range of different OCTA devices, and software vascular detection algorithm, many studies have controversial results on the correlation between FAZ-related indicators and visual acuity before ( 29 , 35 , 42 , 43 ) and after surgery ( 35 , 38 , 43 , 44 ).…”
Section: Discussionsupporting
confidence: 79%
“…Introduced in 2010, 27-gauge vitrectomy has gained popularity for a variety of vitreoretinal conditions, including epiretinal membranes, rhegmatogenous RDs (RRDs), macular holes, and vitreous hemorrhages. 914 It is reported to provide outcomes similar to those of 23-gauge and 25-gauge systems with respect to anatomic success, visual acuity (VA), and postoperative complications. 13,14 The benefits of 27-gauge PPV include faster wound closure, fewer cases of hypotony, and improved patient comfort, even in more complex cases.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The benefits of 27-gauge PPV include faster wound closure, fewer cases of hypotony, and improved patient comfort, even in more complex cases. [9][10][11][12][13][14] The smaller gauge instrumentation used in 27-gauge PPV enables more surgical precision and control because of the smaller distance between the opening of the cutter and the tip of the instrument, which allows the surgeon to use it as scissors during dissection at the retinal surface in diabetic TRD repair. 15 Despite the potential benefits of 27-gauge PPV for diabetic TRD, there has not been wide acceptance of this surgical modality and there is a paucity of outcomes reported in the literature.…”
Section: Introductionmentioning
confidence: 99%